Self-evaluation in women victims of mate violence. - Laura López Angulo; Juan José Apollinaire Pennini; Marlen Array; Addis Moya Ávila (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2006)
Background: The violence against the woman in couple's relationship constitutes one of the main problems of health of the present century. About the relationship of the purely subjective phenomenon, that is the violence, there are not a lot of information; the obtaining of data in this respect constitutes a forced object of study of the Psychology. Objective: to analyze the self-valuation level and self-esteem, in women mistreated in their couple relationship. Methods: It was carried out an observational analytic study, of cases and controls. The sample was conformed by 120 women, 40 forced and 80 that expressed not to have been mistreated, to which the modification of the scale was applied Dembo-Rubinstein and the inventory of self-esteem of Coopersmith. Results and Conclusions: they were statistically very significant and important the differences among the groups. The self-valuation and the self-esteem are presented with different frequencies for the women objects of violence, that were more vulnerables